Public School Multifunctional Resource Rooms In The Northeast Interior: Reflections About Work Conditions And Teachers’ Health - Schott, Marcia; Jardim, Renata; Silva, Noemi Oliveira; Fernandes, Aurélia Emília de Paula (Seven Editora, 2023)
This article reports the quantitative study results that sought to investigate teachers’ health conditions in the Multifunctional Resource Rooms (MRR) in a municipality in the interior of Sergipe state. The field research was carried out in 2018 in 84.6% of institutions with MRR, ten (10) municipal schools and one (1) state school. All participants were women (n=11; 100%) and the majority (90.9%) stated that their previous profession was as teacher. The investigated teachers did not have a high prevalence of diseases and showed high satisfaction with their work; most of them practiced physical activity, did not have depression, and had a good life quality related to their voice. The high motivation for work may be one of the factors in the positive health self-assessment made by the group studied. The findings differ from the working conditions and health found in several investigations with professors described in the literature, signaling the importance of further research about the MRR workers’ health. DOI: https://doi.org/10.56238/methofocusinterv1-104